Uneasy Lies the Head that Bears the Trust: The Effects of Feeling Trusted on Emotional Exhaustion - Baer, Michael D.; Dhensa-Kahlon, Rashpal K.; Colquitt, Jason A.; Rodell, Jessica B.; Outlaw, Ryan; Long, David M. (Academy of Management Journal, 2015)
The construct of feeling trusted reflects the perception that another party is willing to accept vulnerability to one’s actions. Although this construct has received far less attention than trusting, the consensus is that believing their supervisors trust them has benefits for employees’ job performance. Our study challenges that consensus by arguing that feeling trusted can be exhausting for employees. Drawing on Stevan Hobfoll’s conservation of resources theory, we develop a model in which feeling trusted fills an employee with pride—a benefit for exhaustion and performance—while also increasing perceived workload and concerns about reputation maintenance—burdens for exhaustion and performance. We test our model in a field study using a sample of public transit bus drivers in London, England. Our results suggest that feeling trusted is a double-edged sword for job performance, bringing with it both benefits and burdens. Given that recommendations for managers generally encourage placing trust in employees, these results have important practical implications.